Sleep dimensions are associated with obesity, poor diet quality and eating behaviors in school-aged children - Ramírez-Contreras, Catalina; Santamaría-Orleans, Alicia; Izquierdo-Pulido, Maria; Zerón-Rugerio, María Fernanda (Frontiers in Nutrition, 2022)
Objectives: The aim of this cross-sectional study was to investigate the association between sleep dimensions (duration, patterns, and disturbances) with body mass index (BMI), diet quality, and eating behaviors in school-aged children. Additionally, we aimed to investigate whether obesogenic eating behaviors (higher food responsiveness, lower satiety responsiveness, and less slowness in eating) and poor diet quality could mediate the potential association between sleep and obesity in school-aged children. Material and Methods: For all participants (n= 588 children, age 5 – 12 years; 51% girls) we evaluated: sleep dimensions, BMI, diet quality, and eating behaviors (food responsiveness, satiety responsiveness and slowness in eating). Linear regression models were used to test associations between exposure and outcome variables. Additionally, path analysis was conducted to test whether eating behaviors mediated the relationship between sleep and obesity. Results: Shorter sleep duration (B = –0.722, p = 0.009) and greater sleep disturbances (B = 0.031, p = 0.012) were significantly associated with BMI. Additionally, we observed that diet quality was significantly associated with sleep duration (B = 0.430, p = 0.004), the midpoint of sleep (B = –0.927, p = 0.001), and sleep disturbances (B = –0.029, p= 0.001). Among other findings, greater sleep disturbances were associated with food responsiveness (B = 0.017, p < 0.001), satiety responsiveness (B = 0.015, p < 0.001), and slowness in eating (B = 0.012, p < 0.001). Importantly, food responsiveness was found as significant mediator of the relationship between sleep and BMI (R = 0.427, R2 = 0.182, p < 0.001). Conclusions: Late sleep patterns, short sleep duration, and greater sleep disturbances are significantly related to what and how school-aged children eat. Importantly, poor diet quality was significantly related to all three sleep dimensions, while eating behaviors had a significant relationship with greater sleep disturbances. These findings may be relevant to the development of behavioral targets to prevent childhood obesity, including sleep hygiene guidelines as a strategy to improve children’s eating habits, as well as their BMI.